3 in 1 cocoa post-harvest machine / Ellisvianie Gani, Geraldine Ringgau Morris and Mohd Haziq Al-Harith Junaidi - Gani, Ellisvianie; Morris, Geraldine Ringgau; Junaidi, Mohd Haziq Al-Harith (Faculty of Plantation and Agrotechnology, 2023)
Cocoa production around the world are mostly still using manual labour the post-harvest process. It takes more time to complete the operation process in the same time causes lower quantity of yield for cocoa bean production. The aim of this innovation is to help minimizing manual labour during cocoa post-harvest process as well as improvising the mechanization that has already existed in cocoa production. This 3 in 1 post-harvesting working machine includes fermentation, drying and storage process being combined and innovated here.